Pengaruh capital structure, firm size dan profitability terhadap firm value pada perusahaan LQ-45 yang terdaftar di Bursa Efek Indonesia tahun 2021-2024 - Sengkey, Michael; Wokas, Heince R. N.; Korompis, Claudia W. M. (Manajemen Bisnis dan Keuangan Korporat, 2026)
Firm value reflects the market's perception of corporate performance and prospects, influenced by various financial decisions; however, empirical evidence on the direction and consistency of these effects remains inconclusive, particularly among highly liquid companies. This study aims to examine the effect of capital structure, firm size, and profitability on firm value in LQ-45 index companies listed on the Indonesia Stock Exchange for the 2021–2024 period. A quantitative associative approach was employed using secondary data derived from annual financial reports. Samples were selected through purposive sampling, yielding 26 companies from a population of 45, resulting in 75 valid observations after outlier screening. Data were analyzed using multiple linear regression. The findings indicate that capital structure has a significant positive effect on firm value, firm size has a significant negative effect on firm value, and profitability has a significant positive effect on firm value. Simultaneously, all three variables significantly influence firm value. These findings support signalling theory, suggesting that corporate financial decisions serve as signals to investors, and imply that management must balance asset expansion with improved operational effectiveness to optimize firm value.